Użyteczność badań marketingowych w sferze kultury - Niemczyk, Agata (Marketing Research in the Culture, 2007)
The paper is devoted to the problem of marketing research in the field of culture. The author tries to show new conditions for functioning of the cultural institutions. The basis for their activity is market research; serviceableness of The System of Marketing Information. Besides, the author presents the results of research concerning the market of culture.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (3); 2007; nr 1171, s. 44-55